Pengaruh Media Sosial Terhadap Keterampilan Komunikasi Interpersonal Pada Remaja Kota Bandung - Almadina Rakhmaniar (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the effect of social media use on interpersonal communication skills among adolescents in Bandung City. This research uses quantitative method with survey approach. The research sample consisted of 100 randomly selected teenagers. Data were collected through a questionnaire that measured the frequency, duration, type, and purpose of social media use as well as interpersonal communication skills.The results of multiple regression analysis showed that frequency of social media use (B = 0.432, p < 0.001), duration of social media use (B = 0.298, p < 0.01), type of social media used (B = 0.215, p < 0.05), and purpose of social media use (B = 0.148, p < 0.05) all had a positive and significant influence on interpersonal communication skills. The resulting regression model has a coefficient of determination (R²) of 0.572, which indicates that 57.2% of the variability in interpersonal communication skills can be explained by the independent variables used in this study.The findings indicate that social media use significantly affects adolescents' interpersonal communication skills. Frequency of social media use has the greatest influence, followed by duration, type, and purpose of social media use. Therefore, it is important for adolescents to utilize social media wisely in order to improve their interpersonal communication skills.